Early Life Circumstances and Life Cycle Labor Market Outcomes - Manuel Flores; Pilar Garcia-Gomez; Adriaan Kalwij (Tinbergen Institute, 2015)
We investigate how early life circumstances - childhood health and socioeconomic status (SES) - are associated with labor market outcomes over an individual's entire life cycle. A life cycle approach provides insights not only into which labor market outcomes are associated with adverse childhood events but also into whether these associations show up early or only later in working life, and whether they vanish or persist over the life cycle. The analysis is conducted using the Survey of Health, Aging and Retirement in Europe, which contains retrospective information on early life circumstances and full work histories for over 20,000 individuals in thirteen European countries. We find that the associations between early life circumstances and (accumulated) labor market outcomes vary over an individual's life cycle. For men and women, the effect of childhood SES on lifetime earnings accumulates over the life cycle through the associations with both working years and annual earnings. Moreover, for men this association with lifetime earnings reverses sign from negative to positive over their working life. We also find a smaller, positive long-term association between childhood health and lifetime earnings operating mainly through annual earnings and only to a lesser extent through working years, and which is not present at the beginning of the working life for women. Most of these life cycle profiles differ between European country-groups. Finally, for women we find a so-called buffering effect, i.e. that a higher parental SES reduces the negative impact of poor health during childhood on accumulated earnings over the life cycle.
Keywords: D10; I14; J14; J24; J31; O15; 330; Early life circumstances; lifetime earnings; life cycle; SHARE